ANALISIS SISTEM PERSEDIAAN BARANG DAGANG TERHADAP LABA PERUSAHAAN PADA CV DWI KURNIA - Lydia Sumiyati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
On the trading company of course items that are the object is still primarily held goods(purchased) for resale. Such goods are called merchandise inventory.Merchandise inventory recording procedures between one company with another companythat is different. There are systems that use LIFO (last in, first out), ie goods that had been long inthe company that will be sold first. There was also some use the FIFO (first in, first out), ie goods thatenter first in the company's first to be sold anyway.In doing these calculations can be seen the extent to which the effectiveness of thecompany in recording of inventory with a different method. Then how the distribution of merchandiseso they can be up to the hands of consumers so that companies can achieve the optimal profit.